The use of orthopaedic wire for fracture fixation in companion animals - PRASSINOS (N.N. ΠΡΑΣΙΝΟΣ), N. N. (Journal of the Hellenic Veterinary Medical Society, 2017)
Orthopaedic wire is widely used in companion animal fracture repair. It is mainly applied as an auxiliary fixation method, in combination with other orthopaedic implants, and rarely as the sole method of fixation. The most frequently used types of orthopaedic wire are those with both ends straight, and the AO/ASIF wire, which has an "eye" twisted into one end of it, whereas the other end is straight. The wire should be applied tighdy and secured into place, either by a twist knot or by the use of a locking loop, respectively. Three types of wiring can be seen: fullcerclage wire, tension band wire and interfragmentary wires (cruciate or hemi-cerclage). The understanding of the proper principles of orthopaedic wire application and of the limitations of its use with fracture management is crucial. When applied properly and in the correct circumstances, orthopaedic wire is an effective mean of fracture fixation.